2023
DOI: 10.1007/s11214-023-01033-2
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentary Processes on Venus

Lynn M. Carter,
Martha S. Gilmore,
Richard C. Ghail
et al.

Abstract: The sedimentary cycle, including the processes of erosion, transport, and lithification, is a key part of how planets evolve over time. Early images of Venus’s vast volcanic plains, numerous volcanoes, and rugged tectonic regions led to the interpretation that Venus is a volcanic planet with little sediment cover and perhaps few processes for generating sedimentary rocks. However, in the years since the Magellan mission in the 1990s we have developed a better understanding of sedimentary process on Venus. Impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…( 2004 ) reported that Venera descent probe photometry suggested a discrete layer of particulates at 2 km above the mean planetary radius, whose nature is not known and might also be related to volcanic pyroclastic processes (see Carter et al. 2023 , this collection).…”
Section: Clouds and Particulatesmentioning
confidence: 99%
“…( 2004 ) reported that Venera descent probe photometry suggested a discrete layer of particulates at 2 km above the mean planetary radius, whose nature is not known and might also be related to volcanic pyroclastic processes (see Carter et al. 2023 , this collection).…”
Section: Clouds and Particulatesmentioning
confidence: 99%